2013
DOI: 10.1186/1751-0147-55-43
|View full text |Cite
|
Sign up to set email alerts
|

Dairy cows welfare quality in tie-stall housing system with or without access to exercise

Abstract: BackgroundTie-stall housing of dairy cows is used extensively worldwide, despite of the welfare concerns regarding the restriction of voluntary movement and limitation of expression of the cows’ natural behaviour. The aim of this study was to compare the welfare quality of dairy cows kept in two types of tie-stall housing systems: with regular outdoor exercise and without access to exercise. In addition, the study investigated the relationship between different welfare measures of dairy cows kept in tie-stalls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
118
5
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(138 citation statements)
references
References 43 publications
10
118
5
5
Order By: Relevance
“…disease transmission) at the expense of another (e.g. freedom of movement, a key issue of key public concern; Boogaard et al 2011;Popescu et al 2013). Examples abound, but a relevant case for dairy is the calf hutch.…”
Section: Animal-welfare Science: Approaches and Limitsmentioning
confidence: 99%
“…disease transmission) at the expense of another (e.g. freedom of movement, a key issue of key public concern; Boogaard et al 2011;Popescu et al 2013). Examples abound, but a relevant case for dairy is the calf hutch.…”
Section: Animal-welfare Science: Approaches and Limitsmentioning
confidence: 99%
“…In Italy, ''Piedmontese'' cows are traditionally bred in a tie-stall housing system and less frequently in loose housing systems; these systems frequently adopt stalls, and this represents a critical husbandry situation from a welfare point of view, due to the extreme restriction of movement and because the normal behavioural repertoire of the cows is limited (Mattiello et al 2005;Higashiyama et al 2006;Popescu et al 2013). Veissier et al (2008) recommend that cows housed in tiesheds should be given regular access to an exercise area.…”
Section: Introductionmentioning
confidence: 99%
“…However, EFSA did not consider free-stall housing associated with an increased incidence of leg and locomotor disorders as favourable as tie-stalls. Popescu et al (2013Popescu et al ( , 2014 found that loose housing (in cubicles or a straw yard) in Romania have welfare advantages compared to tie-stalls, but they also concluded that welfare is not necessarily poorer in tie-stall housing. Lower incidences of a number of diseases have been found in cubicles than in tie-stalls in Norway, although this difference was not so clear for small free-stall operation (Simensen et al, 2010).…”
Section: Confinement and Restricted Movementmentioning
confidence: 99%